Perilipin 4 in human skeletal muscle: localization and effect of physical activity. Issue 8 (11th August 2015) - Pourteymour, Shirin; Lee, Sindre; Langleite, Torgrim M.; Eckardt, Kristin; Hjorth, Marit; Bindesbøll, Christian; Dalen, Knut T.; Birkeland, Kåre I.; Drevon, Christian A.; Holen, Torgeir; Norheim, Frode
Abstract Perilipins (PLINs) coat the surface of lipid droplets and are important for the regulation of lipid turnover. Knowledge about the physiological role of the individual PLINs in skeletal muscle is limited although lipid metabolism is very important for muscle contraction. To determine the effect of long‐term exercise on PLINs expression, 26 middle‐aged, sedentary men underwent 12 weeks combined endurance and strength training intervention. Muscle biopsies from m. vastus lateralis and subcutaneous adipose tissue were taken before and after the intervention and total gene expression was measured with deep mRNA sequencing. PLIN4 mRNA exhibited the highest expression of all five PLINs in both tissues, and the expression was significantly reduced after long‐term exercise in skeletal muscle. Moreover, PLIN4 mRNA expression levels in muscle correlated with the expression of genes involved in de novo phospholipid biosynthesis, with muscular content of phosphatidylethanolamine and phosphatidylcholine, and with the content of subsarcolemmal lipid droplets. The PLIN4 protein was mainly located at the periphery of skeletal muscle fibers, with higher levels in slow‐twitch as compared to fast‐twitch skeletal muscle fibers. In summary, we report reduced expression of PLIN4 after long‐term physical activity, and preferential slow‐twitch skeletal muscle fibers and plasma membrane‐associated PLIN4 location.